2021
DOI: 10.1136/bjsports-2021-104576
|View full text |Cite
|
Sign up to set email alerts
|

Is cardiac involvement prevalent in highly trained athletes after SARS-CoV-2 infection? A cardiac magnetic resonance study using sex-matched and age-matched controls

Abstract: ObjectivesTo investigate the cardiovascular consequences of SARS-CoV-2 infection in highly trained, otherwise healthy athletes using cardiac magnetic resonance (CMR) imaging and to compare our results with sex-matched and age-matched athletes and less active controls.MethodsSARS-CoV-2 infection was diagnosed by PCR on swab tests or serum immunoglobulin G antibody tests prior to a comprehensive CMR examination. The CMR protocol contained sequences to assess structural, functional and tissue-specific data.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…Four of the studies presented two cohorts [ 8 , 10 , 21 , 31 ]; therefore, we included a total of 33 independent cohorts. Among the 29 included studies, nine were from the USA [ 8 , 15 , 20 , 22 , 24 , 32 , 36 38 ], six were from China [ 10 , 11 , 16 , 18 , 21 , 30 ], three each from the UK [ 19 , 22 , 26 ] and Germany [ 7 , 23 , 28 , 35 ], two each from Italy [ 9 , 27 ] and Turkey [ 29 , 31 ], and one each from Poland [ 17 ], Norway [ 34 ], Hungary [ 33 ] and Spain [ 25 ]. The publication year was 2020 or 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the studies presented two cohorts [ 8 , 10 , 21 , 31 ]; therefore, we included a total of 33 independent cohorts. Among the 29 included studies, nine were from the USA [ 8 , 15 , 20 , 22 , 24 , 32 , 36 38 ], six were from China [ 10 , 11 , 16 , 18 , 21 , 30 ], three each from the UK [ 19 , 22 , 26 ] and Germany [ 7 , 23 , 28 , 35 ], two each from Italy [ 9 , 27 ] and Turkey [ 29 , 31 ], and one each from Poland [ 17 ], Norway [ 34 ], Hungary [ 33 ] and Spain [ 25 ]. The publication year was 2020 or 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The publication year was 2020 or 2021 ( Table 1 ). Ten studies enrolled athletes recovered from COVID-19 [ 8 , 15 , 17 , 20 , 24 , 32 , 33 , 36 38 ] and one study enrolled suspected myocarditis with COVID-19 [ 9 ]. Finally, 10.462 patients with COVID-19, including 1010 non-athletes and 9.452 athletes, and 746 controls were included in our analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study in the British Journal of Sports Medicine , Szabó et al 5 provided a new piece of evidence on the true incidence of myocardial tissue abnormalities at CMR in athletes who tested positive for SARS-CoV-2. The study had many methodological strengths: a large study population; a comprehensive and updated CMR tissue characterisation protocol, including T1 and T2 mapping; the availability of a subset of athletes with both pre-COVID and post-COVID CMR studies; and the inclusion of a cohort of controls without SARS-CoV-2 infection, either athletes or non-athletes.…”
mentioning
confidence: 99%
“… 8 , 9 Furthermore, a controlled cardiac magnetic resonance (CMR) study found definite signs of myocarditis in only 1.4% of athletes. 10 In addition, a recent systematic review concluded that athletes have an overall low risk (0–5%) of pericardial/myocardial involvement after recovery from COVID-19. 11 However, these studies 8–11 were conducted in young athletes (20–25 years), whereas it is known that COVID-19 is most severe at higher age.…”
mentioning
confidence: 99%